2013
DOI: 10.1002/ase.1424
|View full text |Cite
|
Sign up to set email alerts
|

Human Anatomy: Let the students tell us how to teach

Abstract: Anatomy teaching methods have evolved as the medical undergraduate curriculum has modernized. Traditional teaching methods of dissection, prosection, tutorials and lectures are now supplemented by anatomical models and e-learning. Despite these changes, the preferences of medical students and anatomy faculty towards both traditional and contemporary teaching methods and tools are largely unknown. This study quantified medical student and anatomy faculty opinion on various aspects of anatomical teaching at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
0
16

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 56 publications
14
138
0
16
Order By: Relevance
“…Offering learning environments with highly perceived value, and engagement with anatomical material may have the benefit of promoting retention (Lombardi et al, 2014). It is therefore believed that the current use of multimodal teaching approaches at this institution is advantageous and should be encouraged, echoing the sentiments of other researchers (Davis et al, 2014;Johnson et al, 2012;R. Mitchell & Batty, 2009;Sugand et al, 2010).…”
Section: Average Student Final Grades Following the Completion Of Thimentioning
confidence: 96%
See 4 more Smart Citations
“…Offering learning environments with highly perceived value, and engagement with anatomical material may have the benefit of promoting retention (Lombardi et al, 2014). It is therefore believed that the current use of multimodal teaching approaches at this institution is advantageous and should be encouraged, echoing the sentiments of other researchers (Davis et al, 2014;Johnson et al, 2012;R. Mitchell & Batty, 2009;Sugand et al, 2010).…”
Section: Average Student Final Grades Following the Completion Of Thimentioning
confidence: 96%
“…The favorability of lectures is often overwhelming, with students often agreeing that they were more beneficial than self-directed learning (Davis et al, 2014). Despite the push for more active modes of learning, these responses have shown that more traditional modes of delivery cannot be entirely ignored when developing curricula in anatomy and physiology (Choi-Lundberg, Low, Patman, Turner, & Sinha, 2016;Minhas, Ghosh, & Swanzy, 2012).…”
Section: Traditional Approachesmentioning
confidence: 99%
See 3 more Smart Citations